A New Approach to Immunotherapy of Acute Respiratory Infections in Children and to Prevention of Bacterial Complications - Ye.I. Yulish (Zaslavsky O.Yu., 2015)
The paper presents the mechanisms of action of bacterial lysates in acute respiratory infections in children, their importance to activate factors of nonspecific resistance, formation of specific immunity to bacterial agents, which are particularly significant in the origin of respiratory diseases in children.